2015
DOI: 10.3807/josk.2015.19.5.449
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Square-Lattice Photonic Crystal Fiber with Broadband Single-Mode Operation, High Birefringence, and Normal Dispersion

Abstract: In this study we propose a new photonic crystal fiber (PCF) design that simultaneously offers broadband single-mode operation, high birefringence, and large normal dispersion in the optical-communication wavelength regime. The waveguide is based on a hybrid square-lattice PCF (HS-PCF) that has circular air holes of two different diameters alternating in the cladding, plus a pure silica defect at the center. The optical properties of the guided modes are analyzed numerically by the finite-element method (FEM) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Because of its ability to control light in hollow bodies, the loss of blockage is very low and the contact of light is increased, resulting in increased fiber sensitivity [2]. A number of reported works [3][4][5][6][7][8][9][10][11][12][13][14][15][16] have been developed to investigate the performance of optical sensors based on PCF. In several applications, PCF is used, such as gas detection [3][4], chemical detection [5][6], pressure detection [7], biomedical and temperature sensing, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its ability to control light in hollow bodies, the loss of blockage is very low and the contact of light is increased, resulting in increased fiber sensitivity [2]. A number of reported works [3][4][5][6][7][8][9][10][11][12][13][14][15][16] have been developed to investigate the performance of optical sensors based on PCF. In several applications, PCF is used, such as gas detection [3][4], chemical detection [5][6], pressure detection [7], biomedical and temperature sensing, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These bio-sensing and chemical senses play an important role in medical science. As a result, most researchers keep an eye on the detection of fluid, chemical, and gas sensitivities [12][13][14][15][16]. Several numbers of research studies on gas detection were reported.…”
Section: Introductionmentioning
confidence: 99%
“…The growths of photonic crystal fibers (PCFs) with their significant optical properties have confirmed the prospective benefits of optical fibers in chemical and biological sensing [1] [2] [3]. The outstanding characteristics of these micro structured fibers such as small size, freedom of design, and relative compatibility make them stand out for sensing applications [4] [5] [6]. Where in conventional fibers, designing is not so easy, core size is limited, material selec- tion is tough etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several PCF designs for high birefringent and broadband dispersion compensating have been reported [26][27][28][29], but it requires a very sophisticated manufacturing process to realize the reported PCFs because their cross sections are not based on the conventional lattice structure and all air holes are not circular.…”
Section: Introductionmentioning
confidence: 99%